2018
DOI: 10.1038/s41598-018-21961-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Mobilization of Endogenous Bone Marrow Stem Cells Promotes Liver Regeneration after Extensive Liver Resection in Rats

Abstract: Rapid regeneration of the remnant liver is critical for preventing liver failure and promoting recovery after extensive liver resection. Numerous studies have demonstrated the involvement of bone marrow-derived stem cells in liver regeneration and the potential benefits of bone marrow stem cell therapy. To avoid the preparation of stem cells, we proposed in this study to mobilize endogenous bone marrow stem cells pharmacologically with a combination of AMD3100 (A), an antagonist of CXCR4 and low-dose FK506 (F)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Engraftment of CD133 + stem cells in the remnant liver and increased proliferation of hepatic double-stained OV6/Ki67 oval cells was obtained in animals pretreated with combination of two drugs: AMD3100 (Plerixafor or Mozobil) and low dose of FK506 immunosup-pressant. Thus synergistic action of these two drugs resulted in mobilization and recruitment of bone marrow stem cells [10].…”
Section: Pharmacological Mobilization and Recruitment Of Stem/progenimentioning
confidence: 97%
See 2 more Smart Citations
“…Engraftment of CD133 + stem cells in the remnant liver and increased proliferation of hepatic double-stained OV6/Ki67 oval cells was obtained in animals pretreated with combination of two drugs: AMD3100 (Plerixafor or Mozobil) and low dose of FK506 immunosup-pressant. Thus synergistic action of these two drugs resulted in mobilization and recruitment of bone marrow stem cells [10].…”
Section: Pharmacological Mobilization and Recruitment Of Stem/progenimentioning
confidence: 97%
“…For this reason, the pharmacological activation of endogenous stem cells could be a simple and effective method of presenting stem cells to injured liver. In rat model, pharmacological mobilization of bone marrow cells promoting liver regeneration was recently evidenced after extensive liver resection [10]. Engraftment of CD133 + stem cells in the remnant liver and increased proliferation of hepatic double-stained OV6/Ki67 oval cells was obtained in animals pretreated with combination of two drugs: AMD3100 (Plerixafor or Mozobil) and low dose of FK506 immunosup-pressant.…”
Section: Pharmacological Mobilization and Recruitment Of Stem/progenimentioning
confidence: 99%
See 1 more Smart Citation
“…For the alternative regeneration mechanism, bloodborne cells of the bone marrow origin also play a role, in addition to the resident liver cells [11][12][13]. Hepatic stellate cells (HSCs) are also an important element of the liver regeneration machinery being part of liver stem cell niche, supporting regeneration at early stages by producing growth factors and inducing regeneration arrest after restoration of normal organ mass [14].…”
Section: General Mechanism Of Liver Regenerationmentioning
confidence: 99%
“…The source of HPCs remains controversial. Some researchers contend that these cells exist in a quiescent state around bile ducts until activated (Tee, Kirilak, Huang, Morgan, & Yeoh, ; Tee, Smith, & Yeoh, ), while other researchers contend that some HPCs originate from hepatocytes (Wu & Lee, ) or from an extrahepatic source, especially bone marrow (Li et al, ; Zhai et al, ). In addition, recent studies have indicated that HPCs originate from the transdifferentiation of biliary epithelial cells (Raven et al, ).…”
Section: Introductionmentioning
confidence: 99%